2023
DOI: 10.1371/journal.pgph.0001768
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity among women at reproductive age in Cambodia: Data analysis of Cambodia Demographic and Health Survey 2014

Abstract: Overweight and obesity increase the risk of cardiovascular disease, type 2 diabetes mellitus, hypertension, stroke, and some type of cancers, and maternal health globally. In Cambodia, the prevalence of overweight and obesity among women aged 15–49 years increased from 6% in 2000 to 18% in 2014, becoming a public health burden. We examined socio-demographic and behavioral factors associated with overweight and/or obesity among women of reproductive age (WRA) in Cambodia. We analyzed data from the 2014 Cambodia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 26 publications
4
31
0
Order By: Relevance
“…Older aged women were more likely to be overweight or obese as compared to younger women aged 15-19 years. This is consistent with other studies that showed obesity was more prevalent in older WRA [3,27]. The risk of women becoming overweight or obese rises with age, possibly due to unhealthy food consumption and a lack of physical activity [28].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Older aged women were more likely to be overweight or obese as compared to younger women aged 15-19 years. This is consistent with other studies that showed obesity was more prevalent in older WRA [3,27]. The risk of women becoming overweight or obese rises with age, possibly due to unhealthy food consumption and a lack of physical activity [28].…”
Section: Discussionsupporting
confidence: 92%
“…Married women were more likely to be overweight or obese as compared to single women. Similar to previous study on the prevalence of overweight and obesity among WRA and its associated factors utilized CDHS data since 2014 [3], and in line with pooled analysis of DHS data among WRA in Bangladesh, Nepal, and India [29]. The explanation for that could be that married women busy working and take care their children and family may they do not pay more attention to nutritional and physical activity [3].…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations